Utilization of natural resources: Preliminary study on ethnopharmacological application of ‘ulam’ or traditional vegetables among Sama-Bajau of Kampung Menunggui, Kota Belud, Sabah - Awang-Kanak, Fadzilah; Abu Bakar, Mohd Fadzelly; Mohamed, Maryati; Norazlimi, Nor Atiqah (2018)
A preliminary survey on application of ’ulam’ or traditional vegetables for health and food was conducted among Sama-Bajau people from Kampung Menunggui, Kota Belud, Sabah on June 2017 and November 2017. The objective of this study is to document traditional vegetables that have been consumed by the community and further its utilization as herbal medicine. Three respondents were selected using snowball sampling technique, and the data on traditional knowledge on freshly eaten vegetables were collected by semi structured interviews. A total of 33 species from 30 genera, and 19 families of plants and a species of green algae, Caulerpa lentillifera (Caulerpaceae) or locally known as “latok” have been consumed as ’ulam’ or traditional vegetables. Other than being used as food source, 7 species also have been applied as traditional dietary resource and as herbal medicine for postpartum women, treatment for high blood pressure and diabetes , as well as as anti-aging botanicals for health maintenance purposes. The decoction of papaya (Carica papaya) flower and inner bark of coconut (Cocos nucifera) have been eaten fresh to control high blood pressure, leaves of pegaga (Centella asiatica) and the fruit of bitter gourd (Momordica charantia) have been eaten fresh to lower high blood sugar. Young shoots of “buluh” or Bambusa sp., fresh leaves of “ransa ransa” or Cosmus caudatus, and decoction of “kunyit” or Curcuma longa have been utilized as traditional diet and herbal medicine for postpartum women. C. caudatus is also consumed fresh for health maintenance and as anti-aging herbs. Meanwhile the fruit and young leaves of M. charantia have been used as bathing mixture for postpartum recovery, and decoction of C. asiatica has been used to treat jaundice among new born infants. This result provides useful information of traditional knowledge of ulam as traditional dietary resource among the Sama-Bajau people, and also as an approach to preserve their practice of applying ulam as herbal medicine.